OTORHINOLARYNGOLOGICAL SYMPTOMS IN COVID-19 PATIENTS: A COHORT STUDY - Agarwal, Ashish; Akansh Agarwal (Student’s Journal of Health Research Africa, 2024)
Background The COVID-19 pandemic, caused by SARS-CoV-2, has led to widespread infection with a range of clinical presentations, including otorhinolaryngological (ENT) symptoms alongside the more common respiratory manifestations. This study aims to explore the prevalence, types, and clinical significance of ENT symptoms in COVID-19 patients, providing insights into their potential impact on illness severity and patient outcomes. Methods A retrospective observational study was conducted at a tertiary care center, involving 200 COVID-19 patients confirmed via RT-PCR. Patients aged 18 or older without pre-existing chronic ENT conditions were included. Data on demographics, ENT symptoms, other COVID-19 symptoms, and treatment outcomes were collected through patient interviews, medical record reviews, and diagnostic tests. The prevalence of ENT symptoms was calculated, and their association with COVID-19 outcomes was analyzed using descriptive statistics and multivariable logistic regression. Results Among the 200 participants, 56% were male, and 44% were female, with a median age of 45 years. Anosmia and ageusia were linked to a reduced likelihood of severe COVID-19 (OR = 0.5, 95% CI = 0.3-0.7, p < 0.05), while nasal congestion and sore throat were associated with increased severity (OR = 1.7, 95% CI = 1.2-2.4, p < 0.05). Conclusion ENT symptoms, particularly anosmia and ageusia, may serve as clinical indicators of less severe COVID-19, whereas nasal congestion and sore throat may indicate a higher risk of severe outcomes. Recommendations Early recognition of ENT symptoms in COVID-19 can aid in identifying patients at risk of severe disease, guiding treatment strategies, and informing public health interventions to improve patient outcomes. Further research is recommended to elucidate the underlying mechanisms of these associations.